2018
DOI: 10.1037/pas0000643
|View full text |Cite
|
Sign up to set email alerts
|

Spanish translation and validation of the Interpersonal Needs Questionnaire.

Abstract: The present study reports the multistage development and evaluation of a Spanish translation of the Interpersonal Needs Questionnaire (INQ). The INQ measures the constructs of thwarted belongingness and perceived burdensomeness, which the interpersonal theory of suicide proposes are proximal causes of suicidal desire. Participants were bilingual Hispanic college students in the United States (n = 56), heritage Spanish-speaking college students in the United States (n = 281), college students in Spain (n = 1,01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 96 publications
2
36
0
4
Order By: Relevance
“…In particular, in the latter study, both factors resulted positively associated with risk for late-life suicide (i.e., hopelessness, depression, suicidal ideation, and low meaning in life) in U.S. community-dwelling older individuals. More recently, Silva et al (2018) found that thwarted belongingness and perceived burdensomeness are also positively associated with concurrent suicidal ideation (presence-absence and severity) in Spanish-speaking samples. Chu et al (2017) argued that the variability observed across different studies with regard to the validity of the INQ may be due to the different version of the instrument used and the specific characteristics and composition of the samples, challenging the comparability of results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, in the latter study, both factors resulted positively associated with risk for late-life suicide (i.e., hopelessness, depression, suicidal ideation, and low meaning in life) in U.S. community-dwelling older individuals. More recently, Silva et al (2018) found that thwarted belongingness and perceived burdensomeness are also positively associated with concurrent suicidal ideation (presence-absence and severity) in Spanish-speaking samples. Chu et al (2017) argued that the variability observed across different studies with regard to the validity of the INQ may be due to the different version of the instrument used and the specific characteristics and composition of the samples, challenging the comparability of results.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, results from the validation of the INQ‐15 in other cultural contexts showed variable results. A recent validation study in Spanish‐speaking American college students and Mexican inpatients (Silva et al, 2018) found that the original two‐factor model does not represent a good fit, rather a nine‐item, two‐factor measurement model deriving from the elimination of poor fitting items provided better fit across the three samples. In contrast, research conducted in German populations (Glaesmer et al, 2014; Hallensleben et al, 2016) found similar results to the current study, supporting the validity of the 15‐item version of the INQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, para intentar suicidarse o conseguirlo, se requiere una tercera condición, que es la capacidad adquirida, es decir, la facultad de ejecutar acciones para quitarse la vida 22 . Con base en esto, la ideación suicida se explicaría por la carga percibida y la pertenencia frustrada, mientras que la intención suicida, también por la carga percibida y la pertenencia frustrada, así como por la capacidad adquirida 22 , 23 , 24 , 25 , 26 . A efectos del modelo de este estudio, se tomará únicamente la parte de ideación suicida.…”
Section: Introductionunclassified
“…Additionally, the 15‐item version has been modified, with a shortened response scale, for oral administration in the assessment of older adults (Parkhurst et al, 2016). The INQ has been translated into several languages, with psychometric evaluations of several of these translations (German: Glaesmer et al, 2014; Hallensleben et al, 2016; Spanish: Ordoñez‐Carrasco et al, 2018; Silva et al, 2018; Slovene: Podlogar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%